Point prevalence survey to assess antibiotic prescribing pattern among hospitalized patients in a county referral hospital in Kenya - Kamita, Moses; Maina, Michael; Kimani, Racheal; Mwangi, Robert; Mureithi, Dominic; Nduta, Cynthia; Gitaka, Jesse (Frontiers in Antibiotics, 2022)
Antibiotic resistance causes higher morbidity and mortality and higher healthcare costs. One of the factors influencing the emergence of antibiotic resistance is the inappropriate use of antibiotics. Clinical practitioners’ incorrect prescription patterns and a disregard for antibiotic usage recommendations are the leading causes of this resistance. This study examined the antibiotic prescription patterns among hospitalized patients at the Kiambu Level 5 hospital (KL5) to find potential for hospital quality improvement. This study was conducted in July 2021, and all patients hospitalized on the study day were included. The information was extracted from patient medical records using a World Health Organization Point Prevalence Survey (PPS) instrument. Anonymized data was gathered, entered, and then SPSS version 26 was used for analysis. Among the 308 surveyed patients, 191 (62%) received antibiotic medication, and 60.1% of the total were female. The pediatric ward, which had an antibiotic prescription rate of 94.1%, had the highest rate of antibiotic usage, followed by the medical ward (69.2%) and gynecological ward (65.6%). Over 40% of antibiotic prescriptions had a prophylactic medical indication. Penicillin G was the most prescribed antibiotic for community-acquired infections (32.2%), followed by 3rd generation cephalosporins (27.6%) and aminoglycosides (17.2%). Based on the AWaRe classification, 57% of the prescribed antibiotics were in the Access class while 42% were in the Watch class. Incomplete site of indication, lack of a method of administration, and length of administration are some of the conformities that were missing in the medical records. This study shows that antibiotic prescription rates are high, particularly for young patients, and there is a higher risk of antibiotic misuse. The data makes a compelling justification for using antibiotic stewardship practices in Kenyan hospitals.